2008
DOI: 10.1590/s0034-70942008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre bupivacaína racêmica (S50-R50) a 0,125% e bupivacaína em excesso enantiomérico de 50% (S75-R25) a 0,125% e 0,25% em anestesia peridural para analgesia de parto

Abstract: RESUMODuarte NMC, Caetano AMM, Lima LC, Chagas AS -Estudo Comparativo entre Bupivacaína Racêmica (S50-R50) a 0,125% e Bupivacaína em Excesso Enantiomérico de 50% (S75-R25) a 0,125% e 0,25% em Anestesia Peridural para Analgesia de Parto. JUSTIFICATIVA E OBJETIVOS:A peridural contínua é utilizada para alívio da dor do trabalho de parto e associada a baixos índices de complicações. Estudos com enantiômeros levógiros dos anestésicos locais demonstraram maior segurança em função de menor cardiotoxicidade. O objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(19 reference statements)
0
4
1
Order By: Relevance
“…Those results are conflicting with ours since when analyzing the motor blockade we observed that it was similar in both bupivacaine (S75-R25) and ropivacaine groups because there is a predominance of levorotatory isomers in both solutions 13 . Despite in vitro studies having suggested that both isomers of bupivacaine are equipotent for the motor blockade 20 , a more recent in vitro study indicated that that the dextrorotatory is more potent than the levorotatory in inhibiting sodium channels 21 , justifying the presence of lower motor blockade when a mixture with greater concentration o the S isomer is used.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Those results are conflicting with ours since when analyzing the motor blockade we observed that it was similar in both bupivacaine (S75-R25) and ropivacaine groups because there is a predominance of levorotatory isomers in both solutions 13 . Despite in vitro studies having suggested that both isomers of bupivacaine are equipotent for the motor blockade 20 , a more recent in vitro study indicated that that the dextrorotatory is more potent than the levorotatory in inhibiting sodium channels 21 , justifying the presence of lower motor blockade when a mixture with greater concentration o the S isomer is used.…”
Section: Discussioncontrasting
confidence: 85%
“…The present study demonstrated a tendency towards a lower latency in the bupivacaine (S75-R25) group, which might be advantageous in situations in which fast pain relief is desirable such as labor 13 .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Spinal anesthesia performed with fine gauge disposable needles and administration of bupivacaine combined with adjuvant drugs into the subarachnoid space, is reported as effective technique in most caesarean sections [20][21][22]. Previous studies have indicated that administration of epidural bupivacaine in labor analgesia is an advantage because it is coupled with lower intensity of motor blockade [23,24] besides preserving the differential blockade of racemic bupivacaine [25][26][27][28]. The aim of this perspective, double blind randomized study was to evaluate and compare the effectiveness of bupivacaine-fentanyl, bupivacaineclonidine and bupivacaine-dexmetomodine on the quality of blockade and maternal and neonatal repercussions.…”
mentioning
confidence: 99%